2011
DOI: 10.1113/jphysiol.2011.210245
|View full text |Cite
|
Sign up to set email alerts
|

Switching control of sympathetic activity from forebrain to hindbrain in chronic dehydration

Abstract: Non-technical summary Dehydration, a life-threatening condition, occurs when the body does not replace adequate water lost through urination, sweating or when ill with diarrhoea. This presents the body with a major challenge of maintaining blood pressure -essential for consciousness that is dependent on the degree of body hydration, which dictates blood volume. We know that a major control mechanism involves a brain region called the hypothalamus that automatically maintains blood pressure. Our study has descr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
21
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 47 publications
(73 reference statements)
2
21
0
Order By: Relevance
“…Hyperosmolality increases sympathetic nerve activity (2,12,13,52). Even considering that commNTS lesions affect sympathoexcitatory responses (14,34,44,45,55), it is not possible to exclude the participation of sympathetic mechanisms in the residual pressor response in commNTS-lesioned rats treated with intragastric 2 M NaCl.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Hyperosmolality increases sympathetic nerve activity (2,12,13,52). Even considering that commNTS lesions affect sympathoexcitatory responses (14,34,44,45,55), it is not possible to exclude the participation of sympathetic mechanisms in the residual pressor response in commNTS-lesioned rats treated with intragastric 2 M NaCl.…”
Section: Discussionmentioning
confidence: 94%
“…Peripheral osmoreceptors make their first synapse in the NTS (commissural and intermediate) and area postrema (AP) and, according to previous studies (19,28), it was expected a reduction in water intake in commNTS-lesioned rats. Similar to the peripheral osmoreceptor-induced facilitation of water intake, it was recently demonstrated that the commNTS has also an excitatory role in the control of sympathetic nerve activity and arterial pressure during the chronic increase in plasma osmolality produced by 3 days of water deprivation (12). Therefore, other signals and not those from peripheral osmoreceptors might be those that activate the inhibitory mechanisms in the commNTS.…”
Section: Discussionmentioning
confidence: 95%
“…Overexpression of ⌬JunD has been shown to block ⌬FosB-dependent behavioral adaptations associated with cocaine administration in the orbitofrontal cortex (52) and an animal model of posttraumatic stress disease in the nucleus accumbens (51). Dominant negative inhibition of ⌬FosB in the NTS prevents changes in the network control of sympathetic nerve activity that occur during dehydration (16). Therefore, we used the same approach to test the hypothesis that ⌬FosB may have a similar role in activity-dependent changes of magnocellular neurosecretory cells of the SON following BDL.…”
Section: Discussionmentioning
confidence: 98%
“…⌬FosB has a much longer half-life than Fos, resulting in its accumulation with chronic or intermittent stimulation of the CNS (17,25,42) and has been linked to changes in neuronal morphology, receptor expression, and cell signaling related to depression, drug addiction, and other motivated behaviors (24,38,42,45,54). AP-1 transcriptional activity has also been shown to play a critical role in the adaptive control of sympathetic outflow during dehydration (16) indicating that ⌬FosB and other AP-1 proteins may play similar roles in neural networks that regulate vegetative function.…”
mentioning
confidence: 97%
“…This preparation is advantageous as it eliminates the need for anesthetic use, which has been shown to have significant depressive effects on the neural control of autonomic function [44]. We have validated and used this preparation extensively in the past to study the central control of SNA [42,45]. Another advantage of the preparation is the removal of all circulating blood-borne substances such as angiotensin II and other hormones, which can affect sympathetic nerve discharge and obfuscate the data.…”
Section: Discussionmentioning
confidence: 99%